2000
DOI: 10.2527/2000.7882127x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of porcine transcription factors and genes related to fatty acid metabolism in different tissues and genetic populations.

Abstract: Several transcription factors are involved in regulating lipid metabolism in various tissues of animals. Adipocyte determination and differentiation-dependent factor 1 (ADD1), peroxisome proliferator activated receptor alpha (PPAR alpha), and peroxisome proliferator activated receptor gamma (PPAR gamma) regulate both lipogenesis and fatty acid oxidation. We determined the tissue distribution and genetic difference in mRNA concentrations of these transcription factors in two genetic populations of pigs (Newsham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
3
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 0 publications
4
35
3
3
Order By: Relevance
“…As previously reported for human, mouse, and rat tissue distribution studies (Tontonoz et al 1993, Shimomura et al 1997, Kim et al 1998a, we were able to detect ADD1 transcript in pig liver, kidney, lung, ovary, skeletal muscle, adipose tissues, heart, and brain. Our results are in contrast with those of Ding et al (1999Ding et al ( , 2000, who reported ADD1 transcripts to be undetectable in pig kidney and skeletal muscle. In the current study, we used an adult sow to perform tissue distribution analysis, whereas Ding et al (1999Ding et al ( , 2000 used much younger pigs (20-30 kg).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…As previously reported for human, mouse, and rat tissue distribution studies (Tontonoz et al 1993, Shimomura et al 1997, Kim et al 1998a, we were able to detect ADD1 transcript in pig liver, kidney, lung, ovary, skeletal muscle, adipose tissues, heart, and brain. Our results are in contrast with those of Ding et al (1999Ding et al ( , 2000, who reported ADD1 transcripts to be undetectable in pig kidney and skeletal muscle. In the current study, we used an adult sow to perform tissue distribution analysis, whereas Ding et al (1999Ding et al ( , 2000 used much younger pigs (20-30 kg).…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are in contrast with those of Ding et al (1999Ding et al ( , 2000, who reported ADD1 transcripts to be undetectable in pig kidney and skeletal muscle. In the current study, we used an adult sow to perform tissue distribution analysis, whereas Ding et al (1999Ding et al ( , 2000 used much younger pigs (20-30 kg). Thus, it would be of interest to further study pig ADD1 transcripts in these tissues through musculoskeletal maturation.…”
Section: Discussioncontrasting
confidence: 99%
“…The pattern of expression of SREBP-1 we observed in adipocytes, i.e. two bands of approximately 5 kb in length, is similar to that reported for pig adipose tissue (Ding et al 2000, Gondret et al 2001 and for freshly isolated rat adipocytes (Palmer et al 2002).…”
Section: Mechanism Involved In Gh and Insulin Actions On Lipogenesis supporting
confidence: 89%
“…It might be possible that different species and/ or intrinsic depot-specific differences for fat cells contribute to the contradictory results for adipogenesis. For example, conjugated linoleic acid isomer caused an inhibition of differentiation in 3T3-L1 cells [32], but the contrary was found in pig primary preadipocytes [33]. Since data about the effect of ZBTB16 gene on adipogenesis is limited.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 98%